Performance evaluation of parametric models in the hindcasting of wave parameters along the south coast of Black Sea - Akpinar, Adem; Ozger, Mehmet; Bekiroglu, Serkan; Komurcu, Murat Ihsan (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2014)
In the present study, the performances of four parametric models in the wave hindcast were evaluated by comparing with wave measurements at two locations on the Black Sea. Wilson, SPM, JONSWAP, and CEM methods were used to hindcast significant wave height (H-s) and mean wave period (T-g). Wind data required to perform wind-wave hindeasts is gathered by the Turkish State Meteorological Service (TSMS) and the European Centre for Medium-Range Weather Forecast (ECMWF). Wave data set measured at deep water location for Hopa and Sinop buoy stations within the NATO TU-WAVES project was used to validate wind-wave hindeasts. A set of new formulations for wind-wave hindeast was proposed for the Black Sea. Sensitivity analyses were performed for both parametric methods and newly proposed equations. Finally, it is concluded that the CEM method compared to other methods generally produces more accurate results for the hindeasts of wave parameters in both stations. It is observed that parametric methods do not have the sufficiently accurate results in the Black Sea. Proposed formulations cannot produce results at desired level to represent all southern coasts of the Black Sea in comparison to existing parametric methods.
Keywords: Wave hindcasting; Significant wave height; Wave period; Wave statistics; Parametric methods; Black Sea; PREDICTION MODELS; FUZZY; Oceanography